2013
DOI: 10.2139/ssrn.2249956
|View full text |Cite
|
Sign up to set email alerts
|

Export Market Diversification and Productivity Improvements: Theory and Evidence from Argentinean Firms

Abstract: This paper examines the relationship between trade and investment in technology adoption when firms face demand uncertainty. Our model predicts that, for a given overall market size, exporting to several countries reduces firms' demand uncertainty and, hence, raises incentives to invest in productivity improvements. The effects of diversification are heterogeneous across firms: An additional foreign market matters more for firms exporting to fewer destinations. We test the proposed theory using a large sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…A classical paper by Hirsch and Lev (1971) shows, based on a panel of 500 firms from the Netherlands, Denmark and Israel, that firms with more diversified exports have less volatile sales, in line with standard portfolio theory. A more recent study by Juvenal and Monteiro (2013) shows that the exports of Argentinian firms with more diversified exports are more stable. Since volatility can have a strong negative effects on firms and their development, a recent literature has looked at how diversification, through the implied decrease in volatility, can improve productivity (Juvenal and Monteiro, 2013), help to finance investment (Shaver, 2011) or improve profitability (Wagner, 2014).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…A classical paper by Hirsch and Lev (1971) shows, based on a panel of 500 firms from the Netherlands, Denmark and Israel, that firms with more diversified exports have less volatile sales, in line with standard portfolio theory. A more recent study by Juvenal and Monteiro (2013) shows that the exports of Argentinian firms with more diversified exports are more stable. Since volatility can have a strong negative effects on firms and their development, a recent literature has looked at how diversification, through the implied decrease in volatility, can improve productivity (Juvenal and Monteiro, 2013), help to finance investment (Shaver, 2011) or improve profitability (Wagner, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…A more recent study by Juvenal and Monteiro (2013) shows that the exports of Argentinian firms with more diversified exports are more stable. Since volatility can have a strong negative effects on firms and their development, a recent literature has looked at how diversification, through the implied decrease in volatility, can improve productivity (Juvenal and Monteiro, 2013), help to finance investment (Shaver, 2011) or improve profitability (Wagner, 2014). 4 The rest of the paper is structured as follows.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…When compared to the 1990's, in the 2000-2010 period Morocco reached a higher average economic growth with less volatility. A channel through which input tariff reduction may impact growth volatility is by promoting export market diversification, which may reduce demand uncertainty and improve firms' performance, by increasing the incentives to invest(Juvenal and Santos Monteiro, 2013). Although this paper is not going to disentangle any causality between trade and growth, by exploiting the effect on different margins of trade it shows some evidence of the impact of input reduction tariff on export diversification.…”
mentioning
confidence: 83%
“…Hashai (2014) showed that the interplay between 'adjustment costs', 'coordination costs' and within-industry diversification benefits, results in an 'S-curve' relationship between within-industry diversification and firm performance. Juvenal and Paulo (2013) examined the relationship between trade and investment in technology adoption when firms face demand uncertainty. Their model predicted that, for a given overall market size, exporting to several countries reduces firms' demand uncertainty and hence, raises incentives to invest in productivity improvements.…”
Section: Review Of Literaturementioning
confidence: 99%